2022
DOI: 10.1002/slct.202102794
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Supercapacitor Electrode Materials of Mo1‐xCoxS2 Nanoparticles Prepared by Hydrothermal Method

Abstract: Co-doped Mo 1-x Co x S 2 (x = 0, 0.1, 0.3, 0.5) nanoparticles with varying amounts of Co were compounded by hydrothermal channel. The microstructures of the samples were characterized. All the samples showed hexagonal structure, good crystallization, flower shape microspheres and agglomeration to a certain extent. Furthermore, the influence of Co doping on the electrochemical properties was evaluated by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), cycle stability and electrochemical impedance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…When designing an electrode material, the optimal ratio of Mo to heteroatom is often determined, and Table 6 provides data the best achieved cases. The optimal content of Ni or Co in the MoS 2 is 6-7 at% [231,232,247]. A comparative study of MoS 2 nanomaterials doped with Ni, Fe, or Cu in a 6 M KOH electrolyte revealed the pseudocapacitive behavior of the Fe-doped electrode and predominance of electric double-layer capacitance for electrodes doped with Cu and Ni [244].…”
Section: Supercapacitorsmentioning
confidence: 99%
“…When designing an electrode material, the optimal ratio of Mo to heteroatom is often determined, and Table 6 provides data the best achieved cases. The optimal content of Ni or Co in the MoS 2 is 6-7 at% [231,232,247]. A comparative study of MoS 2 nanomaterials doped with Ni, Fe, or Cu in a 6 M KOH electrolyte revealed the pseudocapacitive behavior of the Fe-doped electrode and predominance of electric double-layer capacitance for electrodes doped with Cu and Ni [244].…”
Section: Supercapacitorsmentioning
confidence: 99%